Organic thermally activated delayed fluorescence material with strained benzoguanidine donor - Brannan, Alexander C.; Beaumont, Elvie F. P.; Phuoc, Nguyen Le; Whitehead, George F. S.; Linnolahti, Mikko; Romanov, Alexander S. (Beilstein Journal of Organic Chemistry, 2023)
Organic thermally activated delayed fluorescence (TADF) materials have been widely investigated due to their impressive electronic properties and applied potential for the third generation of organic light-emitting diodes (OLED). We present organic TADF material (4BGIPN) based on the strained benzoguanidine donor and compare it with the benchmark carbazole-based material (4CzIPN). Extended π-conjugation in 4BGIPN material results in yellow-green luminescence at 512 nm with a fast radiative rate of 5.5 × 10−5 s−1 and a photoluminescence quantum yield of 46% in methylcyclohexane solution. Such a nitrogen-rich 4BGIPN material has a significantly stabilized highest occupied molecular orbital (HOMO) at −6.4 eV while the lowest unoccupied molecular orbital (LUMO) at −4.0 eV, indicating potential suitability for application as the electron transport layer or TADF class III emitter in OLEDs.
Keywords: guanidine; organic; photoluminescence; TADF; yellow